Governance in the exploration of global and regional determinants of ICT development - Charles Shaaba Saba; Simplice Asongu; Nicholas Ngepah; Yolande E. Ngoungou (African Governance and Development Institute (AGDI), 2023)
The present study assesses how governance affects information and communication technology at the global level contingent on macroeconomic policy factors such as trade, foreign investment, manufacturing value added and agriculture value added. The focus of the study is on 183 countries for the period 2003 to 2021 and the empirical evidence is based on the generalised method of moments. The following main findings are established. For the full sample, governance unconditionally promotes ICT development while trade openness (industrial added value) moderate governance to promote (dampen) ICT development. In sub-Saharan Africa, only trade openness effectively moderates governance to induce an overall positive effect on ICT while in the MENA, all policy variables moderate governance for an overall positive incidence on ICT sector development. The findings of the MENA are confirmed in the ECA region with the exception of the moderating role of industrial added values which engenders an overall negative effect. In the East & South Asia and the Pacific (ESAP) countries, one overall positive incidence is apparent in the role of trade openness while net negative effects are established from the moderating roles of industrial added value and agricultural added value, respectively. In the American sub-sample, a positive (negative) net effect is apparent from the role of industrial added value (trade) in moderating the incidence of governance on ICT sector development. Policy implications are discussed.
Keywords: G20; O38; O40; O55; P37; 330; ICT; Governance; Trade; FDI; Industry; Agriculture